Daily blood feeding rhythms of laboratory-reared North American Culex pipiens - Megan L Fritz; Edward D Walker; Aaron J Yunker; Ian Dworkin (Journal of Circadian Rhythms, 2014)
Background: Blood feeding by free-living insect vectors of disease is rhythmic and can be used to predict when infectious bites will occur. These daily rhythms can also be targeted by control measures, as in insecticide-treated nets. 'Culex pipiens' form pipiens and 'C.p.' f. molestus are two members of the 'Culex pipiens' assemblage and vectors of West Nile Virus throughout North America. Although 'Culex' species vector human pathogens and parasites, the daily blood feeding rhythms of' C.p'. f. molestus, to our knowledge, have not been studied. We described and compared the daily blood feeding rhythms of three laboratory-reared populations of 'Culex pipiens', one of which has confirmed molestus ancestry. We also examined the plasticity of blood feeding time for these three populations. Results: For most (>70%) 'C.p.' f. pipiens and 'C.p'. f. molestus collected from metropolitan Chicago, IL, blood feeding took place during scotophase. Peak blood feeding occurred in mid-scotophase, 3-6 hours after lights off. For 'C.p'. f. pipiens originating from Pennsylvania, most mosquitoes (> 90%) blood fed during late photophase and early scotophase. 'C.p.' f. molestus denied a blood meal during scotophase were less likely to blood feed during early photophase (< 20%) than were 'C.p'. f. pipiens from Chicago (> 50%). 'C.p'. f. pipiens from Pennsylvania were capable of feeding readily at any hour of photo- or scotophase. Conclusions: Daily blood feeding rhythms of 'C.p'. f. molestus are similar to those of 'C.p.' f. pipiens, particularly when populations originate from the same geographic region. However, the timing of blood feeding is more flexible for 'C.p.' f. pipiens populations relative to 'C.p'. f. molestus.